2005
DOI: 10.1111/j.1365-2885.2005.00681.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of inhibiting cytochrome P450 3A, p‐glycoprotein, and gastric acid secretion on the oral bioavailability of methadone in dogs

Abstract: Methadone is an opioid, which has a high oral bioavailability (>70%) and a long elimination half-life (>20 h) in human beings. The purpose of this study was to evaluate the effects of ketoconazole [a CYP3A and p-glycoprotein (p-gp) inhibitor] and omeprazole (an H+,K(+)-ATPase proton-pump inhibitor) on oral methadone bioavailability in dogs. Six healthy dogs were used in a crossover design. Methadone was administered i.v. (1 mg/kg), orally (2 mg/kg), again orally following oral ketoconazole (10 mg/kg q12 h for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 37 publications
5
52
1
1
Order By: Relevance
“…For these compounds, the marked interspecies difference in oral bioavailability is the result of a high first-pass metabolism in dogs (42,64), a characteristic of oral opiates in dogs that is not as prominent in humans. Other oral opiates not included in this analysis also have essentially zero oral systemic availability in dogs (86,87). For these drugs, systemic clearance exceeds liver blood flow and there may be extrahepatic metabolism contributing to the high first-pass metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…For these compounds, the marked interspecies difference in oral bioavailability is the result of a high first-pass metabolism in dogs (42,64), a characteristic of oral opiates in dogs that is not as prominent in humans. Other oral opiates not included in this analysis also have essentially zero oral systemic availability in dogs (86,87). For these drugs, systemic clearance exceeds liver blood flow and there may be extrahepatic metabolism contributing to the high first-pass metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, it is suggested that morphine is poorly and erratically absorbed from the gastrointestinal tract, particularly following administration of sustained release tablets. These data for morphine are matched by data following oral administration of other opioids to dogs, for example methadone (Kukanich and others 2005a). …”
Section: Options For Medium-term Opioid Analgesia In Discharged Dogsmentioning
confidence: 99%
“…Valspodar was also found to increase the bioavailability and analgesic effects of methadone in rats (148). Conversely, the pharmacokinetics of methadone in dogs was unaffected by P-gp inhibition (221).…”
Section: Methadonementioning
confidence: 96%